Persepsi Remaja Mengenai Pernikahan Dini di Kampung KB Magot, Dusun Pasir Peuteuy, Desa Pawindan, Kabupaten Ciamis - Linashar Arum Truvadi,; Sherly Nurlatifah,; Elsya Syamrotul Hidayat,; Gisella Raisa Madinna,; Yugi Ramadhan Nurfadhil, (Jurnal Bintang Pendidikan Indonesia, 2024)
Based on observations made by researchers at the Department of Community Education, Siliwangi University in 2024, the perception of adolescents regarding early marriage is quite open, shown by most teenagers who are categorized as agreeing enough to prevent early marriage from filling out the questionnaire format. This study aims to find out the perception of adolescents in Magot KB Village, Pasir Peuteuy Hamlet, Pawindan Village, Ciamis Regency regarding early marriage. The research method used is a descriptive quantitative method by distributing questionnaires and assessments based on the Likert scale. Based on the results of research related to adolescents' perception of early marriage, it shows that the data from the results of the questionnaire distribution include the sub-indicator of receiving stimuli getting an average of 4.01 with the conclusion of the category agreeing, the sub-indicator of understanding getting an average of 4.32 with the conclusion of the category strongly agreeing, and the sub-indicator of evaluation getting an average of 4.31 with the conclusion of the category strongly agreeing. The number of the three sub-indicators was accumulated with an average result of 4.21 with the conclusion of the category agreeing. In this case, the counseling activities carried out provide insight and open eyes to teenagers related to early marriage.